Developing a reliable analytical model using ANSYS software to demonstrate the structural and thermal behavior of flat slabs under fire exposure. (Latakia University Journal -Engineering Sciences Series, 2025)
This study presents a clear, reliable, and experimentally consistent method for developing an analytical model for flat slabs using the finite element method. A numerical platform was established using ANSYS software, enabling the analysis of additional parameters specific to flat slabs, such as fire exposure side, concrete characteristic strength, and support conditions. The study also demonstrated a good agreement between the analytical results obtained using the finite element method and the experimental results. Based on the assumptions of the completed analytical research, a reliable and accurate numerical model was developed in comparison to experimental models. This approach helps save time and costs while enabling the investigation of numerous variables with a high degree of reliability in the results.